Someone else’s furniture in one’s own room. An ethnographic return to the center of Tomaszów Mazowiecki - Latocha, Sebastian (A mosaic city: The culture-oriented description, 2023)
The article implements the concept of an anthropological return to the area where ethnographic research was carried out 13 years ago, before the revitalisation of the Tomaszów Mazowiecki town center. The author, inspired by a poem by Julian Tuwim, metaphorically calls the dynamics of the urban landscape “other people’s furniture in one’s own room”. The article is a contribution to research on the poetics of ethnographic return in socio-cultural anthropology.